Constrictive Pericarditis After Lung Transplantation. Issue 5 (May 2020) - Armstrong, Jenna L.; Wojnarski, Charles M.; Choi, Ashley Y.; Hartwig, Matthew G.; Klapper, Jacob A.; Haney, John C.; Milano, Carmelo A.; Daneshmand, Mani A.
Abstract : Background: Constrictive pericarditis is a rare, but increasingly recognized long-term postoperative complication of lung transplantation. Heightened clinical suspicion, improved diagnostic imaging, and effective surgical treatment of the disease have led to progressive awareness of the pathology. We present our institutional experience with constrictive pericarditis after lung transplant in an effort to investigate the cause and natural history of the disease. Methods: From October 2005 to October 2018, 1234 patients underwent orthotopic lung transplantation at Duke University Hospital. An institutional database was queried to identify incident patients and determine baseline clinical data. At a median of 11.2 months (interquartile range = 4.6–28.6 mo), 10 patients (0.8%) developed constrictive pericarditis. Simple descriptive statistics were used to describe cohort characteristics and identify variables associated with constrictive pericarditis after lung transplantation. Results: The indication for transplantation at index operation was idiopathic pulmonary fibrosis in 8 of 10 patients (1.2% of the 760 restrictive lung disease patients transplanted in the same time period). All 10 patients presented with worsening dyspnea and pleural effusions. Right heart catheterization confirmed constrictive physiology in all cases. Eight patients underwent pericardiectomy with improvement in cardiovascular hemodynamics and resolution of symptoms with no 30-day mortality. Conclusions: Diagnosis of constrictive pericarditis should be considered in patients with new-onset heart failure symptoms or recurrent pleural effusions within 2 years of lung transplantation. Idiopathic pulmonary fibrosis may be associated with increased risk for constrictive pericarditis. Pericardiectomy is a safe and effective treatment for posttransplant constrictive pericarditis.